The Impact of Costumer Experience and Electronic Word of Mouth on Brand Trust - Alya Nursakinah; Afif Zaerofi; Shofi Arofatul Marits (Universitas Darussalam Gontor, 2024)
This research aims to find out whether there is an influence of customer experience and electronic word of mouth (E-WoM) on brand trust of local skincare products of Z- Generation living in Jakarta, Bogor, Depok, Tangerang and Bekasi (Jabodetabek). This research uses a descriptive quantitative approach. To collect the data, a questionnaire is distributed to a total of 145 skincare products users. To analyse the data, multiple linear regression analysis is employed. This research shows that customer experience and E-WoM have a positive significant effect on Brand Trust both partially amd simultinously. Keywords: Customer Experience, E-WoM, Brand Trust